A survey on wired and mobile multicast group membership management protocol. (26th May 2009) - Ponnusamy, Vasaki
Multicast is becoming a critical approach in mobile environments, as it ensures the dissemination of services to multiple users simultaneously. In order to deploy mobile multicasts, mobile routing protocol and membership management protocol become essential. As for mobile routing, various mobile ad hoc routing protocols have been proposed and analysed. This paper aims to present a survey on wired and mobile group membership protocols that have been designed by analysing their operation, advantages and disadvantages. This gives an overview of each proposed protocol and an idea of how these features could be adapted into mobile group management protocol.